Intra-Institutional Ziswaf Management at Al-Barokah Islamic Boarding School: A Fiqh Muamalah Review - Muhammad Zuhirsyan; Supaino; Rizal Agus; Sudarsono; Gatot Teguh Arifyanto; Amrin (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyse the contemporary management model of zakat, infaq, sedekah, and waqf (ZISWAF) in the Al-Barokah Islamic boarding school in Simalungun, North Sumatra, from the perspective of muamalah jurisprudence. Theoretical framework: This study is based on the muamalah jurisprudence framework, especially the concept of ownership (al-milkiyyah), trust, benefit (maslahah), and justice ('adl) in the management of social funds. These principles are linked to modern institutional management theory that emphasises accountability, transparency, and efficiency. The integration of classical Islamic legal norms with contemporary management practices is the basis for assessing the effectiveness of the ZISWAF management model in the Islamic boarding school environment. Literature review: The literature review includes Islamic Muamalah Fiqh from an Economic perspective in Islam, Contemporary ZISWAF Management, and Islamic Boarding Schools in the Reality of Sharia Economic Implementation. Methods: This study uses a qualitative approach with a case study method. Data were obtained through interviews with the management of the Al-Barokah Islamic boarding school, documentation of the institution's financial reports, and observations of ZISWAF management practices. Data analysis was carried out through the stages of data condensation, data presentation, and conclusion, using muamalah jurisprudence as an interpretative framework. Results: The study indicates that the ZISWAF management model at the Al-Barokah Islamic boarding school applies a hybrid system that combines fundraising based on traditional religious values ​​with modern institutional management practices. The integration of digital recording systems, participatory decision-making, and empowerment-based fund distribution reflects the application of muamalah fiqh principles in the contemporary context. This model has succeeded in increasing financial transparency, educational independence, and the social welfare of the community around the Islamic boarding school. Implications: These findings indicate that Islamic boarding schools have the potential to become strategic centres of Islamic social finance by institutionalising accountable ZISWAF management in accordance with sharia principles. Novelty: This study introduces the Integrated ZISWAF Management Model (IZMM), which combines the principles of muamalah fiqh with modern management for the sustainable management of Islamic boarding school social funds.